Since it's not an equation, you don't solve it.
If you mean the equation (3x)(x-1)(x-1) = 0, solutions will occur when any factor is 0, i.e. when 3x = 0, x-1 = 0 or x-1 = 0; that is, when x = 0 or 1.
If, rather than solve, you want to simplify this expression, simply multiply out as usual, one factor at a time:
3x (x-1) (x-1)
= 3x (x^2 - x - x + 1)
= 3x (x^2 - 2x + 1)
= 3x^3 - 6x^2 + 3x.
2007-01-10 16:03:28
·
answer #1
·
answered by Scarlet Manuka 7
·
0⤊
0⤋
3x(x-1)(x-1)
this is an incomplete equation, it would be completed by setting it equal to zero.
=> 3x(x-1)(x-1) = 0
=> either 3x = 0 or (x-1) = 1 or (x-1) = 0
=> x = 0 or x = 1 or x = 1
2007-01-11 00:06:00
·
answer #2
·
answered by rishi 2
·
0⤊
0⤋
3x ( x ^ 2 - 2x + 1 ) = 0
3x = 0 or x^2 -2x + 1 = 0
x = 0 or ( x - 1) ( x- 1 ) = 0
x = 0 or x= 1, x = 1.
2007-01-11 00:03:44
·
answer #3
·
answered by sg 2
·
0⤊
0⤋
Are you setting these to zero?
3x=0 gives you x=0
x-1=0 gives x=1
Those are the only two solutions.
2007-01-11 00:01:14
·
answer #4
·
answered by Professor Maddie 4
·
0⤊
0⤋
technically you have 3x*(x-1)squared
which is another way of saying 3x*x-1*x-1
1. combine like terms:
3x*(x-1)=3x squared-1*(x-1)=3x cubed+1
do you understand how i got that? because i combined the ones in the brackets then i collected what i already knew and got an answer of:
3x cubed+1
2007-01-11 00:06:40
·
answer #5
·
answered by rose a 1
·
0⤊
0⤋
I would do the math and come up with 3x^3-3x^2. To know any more you would have to know what it's supposed to equal.
2007-01-11 00:08:18
·
answer #6
·
answered by pacree78 1
·
0⤊
0⤋
Assuming that you want that to equal zero, find the x values that make each one of the factors zero. Namely, 0, 1 and 1 again.
2007-01-11 00:01:35
·
answer #7
·
answered by math_ninja 3
·
0⤊
0⤋
(3x)(x-1)(x-1)=0
then...
3x=0
(x-1)=0
(x-1)=0
therefore...
x=0
x=1
2007-01-11 00:01:21
·
answer #8
·
answered by ~Cyn~ 2
·
0⤊
0⤋
3x times x=3x to second power
3x times negative 1=3x
3x times x=3x to the second power
3x to second power times times 3x to second power= 9x to the fouth power
3x to second power times negative 3x=negative 9x to the third power
negative 3x times 3x to second power=negative 9x to the third power
negative 3x times negative 3x= positive 9x to second power
the final answer:9x to fourth power minus 18x to the third power plus 9x to second power.
2007-01-11 01:44:25
·
answer #9
·
answered by aseel_rteimeh 2
·
0⤊
0⤋
Listen to the teacher in class.
2007-01-11 00:01:18
·
answer #10
·
answered by fyrcracker99 2
·
0⤊
0⤋